New Insights into how HBV Manipulates the Innate Immune Response to Establish Acute and Persistent Infection. Issue 1 (January 2013) - Revill, Peter; Yuan, Zhenghong
The mechanisms by which HBV establishes and maintains chronic infection are poorly understood. Although adult acquired HBV is generally cleared by a robust immune response, most individuals infected at childbirth or in very early childhood develop lifelong chronic infection. In addition, acute infections are unresolved in approximately 5% of individuals infected in adulthood. The host cell mechanisms that ensure establishment and resolution of acute infection and persistent infection remain unclear. Currently, two schools of thought suggest that either HBV is a 'stealth' virus, which initially establishes infection by avoiding host innate immune responses, or that HBV facilitates initial infection and progression to persistence by actively manipulating the host innate immune response to its advantage. There is increasing evidence that activation of innate host cell signalling pathways plays a major role in limiting adult acquired HBV infection and that, in turn, HBV has evolved numerous strategies to counteract these defence mechanisms. In this review, we summarize current knowledge regarding innate immune responses to HBV infection and discuss how HBV regulates cell signalling pathways to its advantage, particularly in the setting of chronic HBV infection. In turn, we show how an intimate knowledge of innate immune responses is driving development of novel therapeutic agents to treat chronic HBV infection.